They called me slut the process of shaming and its influence on the self-concept and sexual reputation of teenage girls. - Bahinting, Katrina F.
This phenomenological study explored women?s slut-shaming experiences in school, how they managed the ?slut? label and how the label influenced their self-concept and sexual reputation. Three college students from Bacolod City, Negros Occidental were interviewed for this project. The participants aged 18-23 years have experienced slut-shaming incidents in school. The methodology for this study consisted of conducting in-depth interviews exploring the slut-shaming incidents in school. The methodology for this study consisted of conducting in-depth interviews exploring the slut-shaming experiences of the participants and Rosenberg?s Self-Esteem Scale to measure the participants? current self-esteem. The data gathered on the experiences encountered by slut-shamed girls were recorded, transcribed and analyzed using Bedevilment and Labeling Process by John Curra (1994). The results of the study showed that factors which led to slut-shaming include individual characteristics, flirting style and sexual activity. Two forms of slut-shaming experiences in school emerged from the data gathered: being gossiped and ostracism. Furthermore, the label management of the participants which includes embracing, ignoring and moving away from the label, was influenced by the degree of importance of the labelers and the girls? own perception of a slut. The data showed that the shamed individuals had positive and negative self-concept after shaming and was seen as someone who was sexually dirty. In conclusion, the influence of shaming to the girls? self-concept varies depending on how the shamed individual manages the slut label.